Strategic planning documents as a tool for eliminating interregional differentiation of socio—economic development - I. A. Andreeva; V. I. Menshchikova (Путеводитель предпринимателя, 2020)
The article examines the main strategic documents of the Russian Federation: national projects, state programs aimed at reducing the level of interregional differences in regions. The assessment of the positions of the regions of Russia in the rating by the quality of life is carried out. Conclusions are made about the effectiveness of the implementation of state programs in areas related to balanced regional development and quality of life. The main shortcomings of the strategy of spatial development of the Russian Federation are revealed and the necessity of using additional tools aimed at reducing the lag in the rates of socio–economic development for a number of regions is substantiated.